Análisis Jurídico Doctrinario sobre: la existencia de muchos partidos no garantiza la participación democrática en Ecuador - Patiño Ponce, Karla Mireya (2023)
The present investigation entitled "Doctrinal Legal Analysis on the many political parties ́ existence does not guarantee democratic participation in Ecuador", has as its general objective to carry out a conceptual, legal, and comparative analysis of the existence of many political parties and movements in Ecuador and since this becomes a problem in the electoral processes of its history. There has always been a considerable number of political organizations, and sixteen binomials presented candidacies for the last presidential elections that were held in Ecuador. This is a high number considering the number of inhabitants and the extension of our territory, and an obvious problem that must be considered by legislators, since the excessive number of these does not facilitate the voters ‘decision, but on the contrary, makes it difficult the right to vote, indirectly forcing them to take care of themselves in the face of an irresponsible vote. Demonstrating that the many political party’s existence does not guarantee democratic participation in Ecuador, will be achieved through an analysis of relevant regulations, such as the Republic Constitution, and the Organic Law of Participation-Code of Democracy, among others. A study of other legislation and electoral processes has also been carried out, it is also intended to demonstrate that financing all these political parties limits the State's attention to other priority needs of citizens. Thanks to the research study, it was also possible to show that there is little control by the National Electoral Council, within political organizations, and that the citizens democratic participation is not fully guaranteed, taking into account that the Electoral processes can only participate members of political organizations or representatives of the same, registered by the organizations.